El Círculo de Recreo de Valladolid (1931-1950) - Rafael Serrano García (Mélanges de la Casa de Velázquez)
This article proposes an explanation of the decline and revival of the Círculo de Recreo of Valladolid between 1931 and 1951, as possibly representing the evolution of other recreational organisations in Castile and Leon, and in Spain generally, during that period. On the one hand it discusses the steady decline of membership and revenue up until the Civil War and its recovery after the end of the war, when a relaxation of the strictly elitist system of screening allowed a new influx of members and the range of services offered was made more attractive. On the other hand it points to the presence of highly diverse political currents in society at large and the general politicisation during the years of the Republic, with an increasingly cliquish tendency; and also the fact that despite the involvement of the Círculo in support for the rebels, there was some friction with the new authorities because of the tenacious monarchist sympathies espoused by many of the club’s members.